Acute adrenal failure as the presenting feature of primary antiphospholipid syndrome in a child - Improda Nicola; Alessio Maria; Capalbo Donatella; Russo Giustina; D'Acunzo Ida; Palamaro Loredana; Pignata Claudio; Salerno Mariacarolina (BMC, 2012)
Abstract Introduction Antiphospholipid syndrome (APS) is characterized by recurrent arterial and venous thrombosis and detection of antiphospholipid antibodies (aPLs). This syndrome may be associated with connective tissue disorders, or with malignancies, but it may also appear in isolated form (primary APS). We report on a pediatric patient presenting with acute adrenal failure as the first manifestation of primary APS. Case report A previously healthy 11-year-old boy developed fever, abdominal pain, and vomiting. An abdominal computed tomography scan showed nodular lesions in the adrenal glands. He was referred to our Department and a diagnosis of APS and acute adrenal failure was considered, based on positive aPLs (IgG and IgM), elevated ACTH levels and low cortisol levels. Other features were anemia, thrombocytopenia, elevated inflammatory parameters, hypergammaglobulinemia, prolonged partial thromboplastin time, positive antinuclear, anticardiolipin, anti-platelet antibodies, with negative double-stranded DNA antibodies. Lupus anticoagulant and Coomb's tests were positive. MRI revealed a bilateral adrenal hemorrhage. A treatment with intravenous metylprednisolone, followed by oral prednisone and anticoagulant, was started, resulting in a progressive improvement. After 2 months he also showed hyponatremia and elevated renine levels, indicating a mineralcocorticoid deficiency, requiring fludrocortisones therapy. Conclusion The development of acute adrenal failure from bilateral adrenal haemorrhage in the context of APS is a rare but life-threatening event that should be promptly recognized and treated. Moreover, this case emphasizes the importance of the assessment of aPLs in patients with acute adrenal failure in the context of an autoreaction.